CalliphoraRomantis: Discovery of A New Species in The Field of Forensic Entomology - Pregonas, Elijah; M. Mc Gowan, Josh (Journal of Advanced Forensic Sciences, 2023)
Over the years, different entomological genera have been found for forensic analysis. Their biological cycles and how they interact with decomposing bodies have become known. But it is when it comes to identifying a species that problems arise. Firstly, to analyses a corpse, there is a minimum of ethical laws, without which the study would be impossible. On the other hand, these species vary according to geographical and climatic zones. Therefore, what is studied in one place will not be the same as what is studied in another, which has different characteristics. In this study we want to present one of the recently found species and how it was found.
Keywords: New species; climate; humidity; crime; forensic analysis.